Study of the growth process and optoelectrical properties of nanocrystalline Cu3BiS3 thin films (2010)
Cu3BiS3 thin films were prepared on soda?lime glass substrates by co?evaporation of the precursors in a two?step process; for that, the metallic precursors were evaporated from tungsten crucibles in the presence of elemental sulphur evaporated from a tantalum effusion cell. The films were characterized by spectral transmittance, Atomic Force Microscopy, X?ray Photoelectron Spectroscopy, Scanning Electron Microscopy and electrical measurements to investigate the effect of growth conditions on the optical, morphological and electrical properties. The results revealed that the Cu3BiS3 films present p?type conductivity, a high absorption coefficient (greater than 104 cm–1), and an energy band gap, Eg, of about 1.39 eV. We observed from Atomic Force Microscopy and electrical measurements that grain size and electric conductivity of the Cu3BiS3 samples are influenced by the copper mass ratio in this material. We found, in the high?temperature range above room temperature, that carrier transport is thermally activated with activation energies fluctuating between 0.17 and 0.28 eV. This suggests that this compound has good properties to perform as absorbent layer in thin?film solar cells.